MCSE study guide : Windows 95 and networking essentials - Casad, Joe, 1958-.; Chisholm, Leigh Anne.; Heywood, Drew.; McLaren, Tim.; Wolfe, Mike. (Indianapolis, IN : New Riders, 1996)
Windows 95; Networking essentials.
Includes index.
Keywords: Computers; Microsoft Windows (Computer file) -- Examinations -- Study guides; Operating systems (Computers) -- Examinations -- Study guides; Computer networks -- Examinations -- Study guides; Electronic data processing personnel -- Certification